Mapping the oxygen structure of γ-Al(2)O(3) by high-field solid-state NMR spectroscopy - Wang, Qiang (Nat Commun, 2020)
γ-Al(2)O(3) is one of the most widely used catalysts or catalyst supports in numerous industrial catalytic processes. Understanding the structure of γ-Al(2)O(3) is essential to tuning its physicochemical property, which still remains a great challenge. We report a strategy for the observation and determination of oxygen structure of γ-Al(2)O(3) by using two-dimensional (2D) solid-state NMR spectroscopy at high field. 2D (17)O double-quantum single-quantum homonuclear correlation NMR experiment is conducted at an ultra-high magnetic field of 35.2 T to reveal the spatial proximities between different oxygen species from the bulk to surface. Furthermore, 2D proton-detected (1)H-(17)O heteronuclear correlation NMR experiments allow for a rapid identification and differentiation of surface hydroxyl groups and (sub-)surface oxygen species. Our experimental results demonstrate a non-random distribution of oxygen species in γ-Al(2)O(3).